ENT600: Availability of fresh food at FamilyMart SS15 for customers’ satisfaction / Damia Kamilia Ahmad, Luqman Hariz Shaarani and Muhammad Luqman Ismadi. - Ahmad, Damia Kamilia; Shaarani, Luqman Hariz; Ismadi, Muhammad Luqman (2018)
FamilyMart in SS15 is a popular convenience store where most people especially teenagers and young adults go to obtain freshly prepared snacks. However, our observation implies that the fresh food sells out quickly and is no longer available for the day. The problem leads the team to analyze the issue on the availability, selling and purchasing method of fresh food in FamilyMart in SS15. This study's research method uses survey analysis conducted via questionnaires handed to random customers at a certain time. The answers revealed dissatisfaction and disappointment among the customers towards the constant unavailability of the freshly prepared food items. The observation leads the team to a further discussion and come out with a solution on making it easier for customers to know the availability of the fresh food and pre-order food items. The team recommended on establishing an application which notifies the users whether the required item is available, the amount of the item and when will it be available. The limitations to this study is that most of the customers in the SS15 FamilyMart are college students.